Pengaruh Workshop Penyusunan Artikel dan Strategi Publikasi Terhadap Pemahaman Mahasiswa (Studi Kasus di Sekolah Tinggi Ilmu Ushuluddin Darussalam Bangkalan) - Fatichatus Sa’diyah; Abd. Muin (Badan Penerbit STIEPARI Press, 2025)
Many students have minimal knowledge about how to write scientific articles. Therefore, intensive training and guidance are needed so that they are more proficient. In addition, it is important to analyze the results of the training. The author will discuss the effect of article writing workshops and publication strategies on the understanding of 6th semester students at the Ushuluddin Darussalam Bangkalan College of Science. This study uses a quantitative method with a case study approach. The author also includes a quasi-experimental approach to test the causal relationship between the variables studied. In this approach, a pre-test and post-test were conducted which must be filled out by all sixth semester students before and after the workshop. The results showed that students' understanding of the material increased. Before the workshop, the average pre-test score of students was 55.06, and after the workshop it increased to 60.94. Although there was an increase, the change was not too large. The average n-gain value of 0.13 indicates a small increase in students' understanding, which is included in the low category. Article writing training is very important to improve the quality of students' research and scientific publications. The results showed that the workshop had a positive effect, although there was still room for improvement. Therefore, it is suggested that this training be conducted routinely to support students' ability in writing articles and mastering publication strategies in the future.